2021
DOI: 10.3167/latiss.2021.140203
|View full text |Cite
|
Sign up to set email alerts
|

The irony of an ‘international faculty’

Abstract: Using the autoethnographic case study method, this article examines how my positionality as a foreign-born faculty member intersects with the institutional rhetoric of diversity and inclusion present in many predominantly White institutions. My vignettes show that foreign-born faculty, although contributing to the representation of diversity numbers, are positioned as knowledge providers in the discussions about the ‘global’, the ‘cultural’ and sometimes the ‘racial’, thus, ironically reinforce the embedded Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have shed some light on the experiences of foreign-born academics in the United States demonstrating that both gender and national origin may create challenges for international women faculty. In terms of methodology, prior research mainly employed interviews (e.g., Ghosh & Barber, 2021;Li, 2020) or autoethnographies (e.g., Cruz et al, 2020;Wang, 2021). This study employed a quantitative approach and drew on survey data, which will later be supplemented with interview data within our larger, mixed-methods interdisciplinary project.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shed some light on the experiences of foreign-born academics in the United States demonstrating that both gender and national origin may create challenges for international women faculty. In terms of methodology, prior research mainly employed interviews (e.g., Ghosh & Barber, 2021;Li, 2020) or autoethnographies (e.g., Cruz et al, 2020;Wang, 2021). This study employed a quantitative approach and drew on survey data, which will later be supplemented with interview data within our larger, mixed-methods interdisciplinary project.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, racial minorities face marginalization on university campuses (Agosto and Karanxha, 2011; Davis and Brown, 2017; Wang, 2021). The National Center of Education Statistics (NCES) found that black people, who constitute 12% of the US population, constitute 6% of faculty in degree-granting postsecondary institutions as of Fall 2018 (NCES, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This involves both recruiting students from diverse backgrounds and employing faculty from multicultural backgrounds. Research shows that faculty members of foreign descent tend to reflect the changing demographics of the internationalized campus environment, and bring diversity in experience and ideas to the American education ethnos (Hénard et al, 2012; Immigrant black female faculty Wang, 2021). Institutions that incorporate foreign academic professionals and students help to promote cultural competency and position graduates to work in multicultural environments (Gordon et al, 2019;Hurtado, 2001;Trice, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation